2007
DOI: 10.1016/j.bbamcr.2007.03.023
|View full text |Cite
|
Sign up to set email alerts
|

The small GTPases Rab5 and RalA regulate intracellular traffic of P-glycoprotein

Abstract: P-glycoprotein (P-gp) is a plasma membrane glycoprotein that can cause multidrug resistance (MDR) of cancer cells by acting as an ATP-dependent drug efflux pump. The regulatory effects of the small GTPases Rab5 and RalA on the intracellular trafficking of P-gp were investigated in HeLa cells. As expected, overexpressed enhanced green fluorescent protein (EGFP)-tagged P-gp (P-gp-EGFP) is mainly localised to the plasma membrane. However, upon cotransfection of either dominant negative Rab5 (Rab5-S34N) or constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 44 publications
2
29
0
Order By: Relevance
“…Although mitochondria localization of P-gp was reported (Munteanu et al, 2006), co-localization of P-gp-EGFP or wild-type P-gp with mitochondrial marker were not observed (Fu et al, 2007, Paterson and Gottesman, 2007). The sites of P-gp synthesis (ER), modification (Golgi), trafficking/recycling (endosomes) and degradation (lysosome, co-localized with LAMP1/2) are indicated in Figure 2.…”
Section: Intracellular Localization Of P-gpmentioning
confidence: 99%
See 2 more Smart Citations
“…Although mitochondria localization of P-gp was reported (Munteanu et al, 2006), co-localization of P-gp-EGFP or wild-type P-gp with mitochondrial marker were not observed (Fu et al, 2007, Paterson and Gottesman, 2007). The sites of P-gp synthesis (ER), modification (Golgi), trafficking/recycling (endosomes) and degradation (lysosome, co-localized with LAMP1/2) are indicated in Figure 2.…”
Section: Intracellular Localization Of P-gpmentioning
confidence: 99%
“…Similarly, increased intracellular wild type P-gp was also observed in multidrug resistant MCF-7/Adr cells transfected with Rab5-S34N, suggesting that Rab5 regulates P-gp traffic from the endosome compartment to the plasma membrane in nonpolarized cells (Fu et al, 2007). However, studies in LS174T cells, showed that overexpression of Rab5 resulted in removal of P-gp from the plasma membrane into intracellular compartments, suggesting that Rab5 regulates P-gp endosytosis in these cells (Kim et al, 1997).…”
Section: Intracellular Traffic Of P-gpmentioning
confidence: 99%
See 1 more Smart Citation
“…In simple non-polarized cells, internalized membrane proteins are first delivered to Rab family of small GTP-ases (Rab, Ral, Rac), known to regulate vesicle traffic from a specific organelle or along a specific pathway [64] to endosome-endosome tethering and fusion [65][66][67][68]. Recently it has been shown that over-expression of Rab5 and RalA GTPase accelerate intracellular trafficking of P-gp, and consequently intracellular levels of daunorubicin, a substrate of P-gp, clearly demonstrating that these small GTPases are involved in P-gp plasma membrane localization, and endocytosis [69]. Furthermore, they showed that increased intracellular P-gp was found in early endosomes, according to Kim et al [15] who previously demonstrated that endocytic/recycling traffic of P-gp is involved in steady-state distribution of transporters and this consequently influences drug resistance of cancer cells.…”
Section: P-glycoproteinmentioning
confidence: 99%
“…[2527,54,6365] Images of conjugate 11 [P-(AP-FITC)-mAb] incubated with A2780/AD cells does exhibit limited internalization within the cells, and based on trafficking studies of Pgp in the literature, it is within early endosomes or lysosomes, and not within recycling endosomes. [6,64] If alteration of Pgp trafficking had occurred, a more intense fluorescence near the perinuclear region, as found for conjugate 10 [P-(AP-FITC)], would be evident. [20,40] Localization of HPMA copolymer conjugates was studied using FITC labeled conjugates, rather than DOX, as alterations in DOX fluorescence occur due to DNA intercalation, effects of the cell medium, whether the cells are sensitive or resistant to anti-cancer agents and the presence of DOX metabolites.…”
Section: Discussionmentioning
confidence: 99%